LGG-30. EVALUATING PEDIATRIC SPINAL LOW-GRADE GLIOMAS-A 30-YEAR RETROSPECTIVE ANALYSIS. Issue 2 (22nd June 2018) - Carey, Steven; Sadighi, Zsila; Wu, Shengjie; Chiang, Jason; Ghazwani, Yahya; Acharya, Sahaja; Boop, Fredrick; Gajjar, Amar; Qaddoumi, Ibrahim
Abstract: Most pediatric spinal tumors are low-grade gliomas (LGGs). Characterization of these tumors has been difficult given their heterogeneity and rare incidence. Spinal tumors diagnosed in pediatric patients at our institution between 1984 and 2014 were reviewed retrospectively. Demographics, clinical presentation, pathology, imaging, management, and late effects were examined. Of the 730 patients with LGG, forty patients (5.5%) had spinal tumors, twenty-four (60%) of which were pilocytic astrocytomas. The most common initial presentations were pain (n=15), partial extremity paralysis (n=13), and ataxia (n=11), with the diagnosis frequently delayed by months and sometimes years (range: <1 week to 6 years). Seventy-five percent of tumors were at least partially resected, and more than half of those resected required adjuvant therapy with chemotherapy (n=10) or radiation (n=7). Nine other patients received a biopsy for histologic diagnosis and were treated with either chemotherapy (n=3) or radiation (n=5) or only followed (n=1). Tumor progression was noted in 35% of the patients, mostly locally; and 10 of 14 underwent salvage therapy (repeat surgery, radiation, or chemotherapy) without further progression. During the evaluation period (median follow-up: 7 years), two patients died, both secondary to tumor progression. Long-term sequelae of the disease/treatment were mostly residual neurologic deficits (paresthesia, paralysis), chemotherapy-induced hearing loss, and scoliosis. In conclusion, spinal LGG is a rare entity with significant long-term effects. Due to the tumors' relatively slow growth and non-specific presentation, their diagnosis is frequently delayed, which could negatively affect the long-term sequelae in patients with these tumors.